An Optimized Microplate Assay System for Quantitative Evaluation of Plant Cell Wall-Degrading Enzyme Activity of Fungal Culture Extracts - King, B.C.; Donnelly, M.K.; Bergstrom, G.C.; Walker, L.R.; Gibson, D.M.
Developing enzyme cocktails for cellulosic biomass hydrolysis complementary to current cellulase systems is a critical step needed for economically viable biofuels production. Recent genomic analysis indicates that some plant pathogenic fungi are likely a largely untapped resource in which to prospect for novel hydrolytic enzymes for biomass conversion. In order to develop high throughput screening assays for enzyme bioprospecting, a standardized microplate assay was developed for rapid analysis of polysaccharide hydrolysis by fungal extracts, incorporating biomass substrates. Fungi were grown for 10 days on cellulose- or switchgrass-containing media to produce enzyme extracts for analysis. Reducing sugar released from filter paper, Avicel, corn stalk, switchgrass, carboxymethylcellulose, and arabinoxylan was quantified using a miniaturized colorimetric assay based on 3,5-dinitrosalicylic acid. Significant interactions were identified among fungal species, growth media composition, assay substrate, and temperature. Within a small sampling of plant pathogenic fungi, some extracts had crude activities comparable to or greater than T. reesei, particularly when assayed at lower temperatures and on biomass substrates. This microplate assay system should prove useful for high-throughput bioprospecting for new sources of novel enzymes for biofuel production.
Keywords: BIOETHANOL; BIOMASS CONVERSION; CELLULASE; CELL WALL HYDROLYSIS; HIGH THROUGHPUT SCREENING; PLANT PATHOGENS